Avaliação da atividade antioxidante e da inibição da enzima α-glicosidase presente no chá das folhas de Coffea arabica - Nascimento, Gerlan Oliveira do (2019)
Diabetes is a metabolic disorder characterized by insulin production deficiency or/and its action, being inhibition of the α-glucosidase enzyme one of the forms of treatment. Studies have shown that the coffee leaves of the Coffea arabica species possesses antioxidant and anti-diabetic properties. This work evaluates the pharmacological potential of C. arabica leaves aqueous extract prepared from microwave oven. The chemical analysis began with the identification and quantification of the phenolic compounds of tea by High-Performance Liquid Chromatography. The next step was to investigate, in vitro, the total phenolic content (TFC), the antioxidant activity (AA), the effect on the α-glucosidase enzyme assays, in relation to acarbose and finally evaluate the ability to inhibit 50% of activity (IC50). In general, the coffee leaves presented results equal to 53.74 ± 0.02 mg EAG/g and 46.65 ± 0.002 mg.mL–1 respectively for TFC and AA which were satisfactory when compared to other commonly consumed teas. As to the α-glucosidase enzyme, mangiferin, rutin and aqueous extract, they inhibited, respectively, 90.42%, 85.71% and 85.92% of their activity. Aqueous extract IC50 was 0.086 mg.mL–1 62 times lower than the IC50 of acarbose. This high inhibitory power can be attributed to the synergism of the phenolics present and since it is a natural product, it does not present undesirable side effects. Thus, the results indicate that the tea of coffee leaves of C. arabica species, besides an antioxidant beverage, is also potentially useful for the inhibition of the α-glucosidase enzyme.